Coiling and clipping of middle cerebral artery aneurysms: a systematic review on clinical and imaging outcome. (27th November 2014) - Zijlstra, IJsbrand A; Verbaan, Dagmar; Majoie, Charles B; Vandertop, Peter; van den Berg, Rene
Abstract : Background: There is an ongoing debate on the preferred treatment of middle cerebral artery (MCA) aneurysms. The purpose of this study was to assess the clinical and imaging outcomes comparing conventional coiling and clipping of unruptured and ruptured MCA aneurysms. Methods: We searched the electronic databases PubMed, EMBASE, and Cochrane from January 1990 to May 2014. Results: 51 studies were included in the analysis. Favorable outcome was reported in 97.0% and 77.1%, and in 97.2% and 72.8% of patients after coiling and clipping of unruptured and ruptured aneurysms, respectively. Death rates were 1.1% and 8.4% after coiling and 0.3% and 14.7% after clipping of unruptured and ruptured aneurysms, respectively. Initial adequate occlusion was obtained in 89.6% and 92.1% after coiling of unruptured and ruptured aneurysms, respectively. Only three studies on clipping reported on aneurysm occlusion during follow-up. Conclusions: Both coiling and clipping are procedures with low mortality and morbidity rates and, although it may seem that coiling is better for ruptured aneurysms and clipping for unruptured aneurysms, no firm conclusions can be drawn due to the variation in study design and lack of standardized reporting on MCA aneurysm treatments. Standardized observational studies from prospectively kept databases are needed to allow stronger conclusions to be drawn on what is the best treatment for MCA aneurysms. Comparable with aneurysms in other locations, a multidisciplinary approach is therefore recommended with selection of treatment modality based on the clinical condition of the patient and the morphological aspects of the aneurysm.